A Review of the Biological Roles of MiR-4800; A Novel Tumor Biomarker with Therapeutic Potential - Monireh Khordadmehr; Reyhaneh Matin; Behzad Baradaran; Amir Baghbanzadeh; Farinaz Jigari-Asl; Farzad Katiraee (Tabriz University of Medical Sciences, 2022)
MicroRNAs (miRNAs) are known as a group of short noncoding ribonucleic acids (ncRNAs). Mainly, they can manage gene expression at the posttranscriptional level in the essential biological and physiological functions. Significantly, more than 50% of the discovered miRNAs genes are placed in cancer‐related genomic regions, which can act as oncomiR or oncosuppressor. In this regard, growing evidence recently demonstrated the deregulation of miR-4800 in human cancers and non-cancerous diseases. However, little information is available on the biological roles of miR-4800 in cancer initiation, development, and progression. Here, we reviewed the targeting sites and biogenesis functions of the miR‐4800 family in physiological and pathological processes like human cancers, particularly with a particular focusing on the validated specific targets.